Digital Payment Adoption and MSME Competitiveness in Indonesia: The Roles of Transaction Efficiency, Financial Inclusion, and Business Performance - Awal Nopriyanto Bahasoan; Wahdaniah Wahdaniah; Muh. Faisalrahmat; Yuspina Tandilintin; Yeni Pratiwi Bulo (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The adoption of digital payments, particularly through the Quick Response Code Indonesian Standard (QRIS) and a range of financial technology (fintech) instruments, has expanded rapidly as a catalyst for the transformation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Yet, the literature linking such adoption to MSME competitiveness remains fragmented across disciplines and theoretical frameworks. This study aims to map the intellectual and thematic structure of that literature and to formulate an integrative model explaining the roles of transaction efficiency, financial inclusion, and business performance. The method is a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol and combined with bibliometric analysis, comprising performance analysis and science mapping using VOSviewer, applied to 177 Scopus-indexed documents published between 2018 and 2026. The results reveal exponential publication growth peaking in 2024 to 2025, a strong dominance of Indonesian affiliations, and 1,620 total citations with a corpus h-index of 21. Keyword co-occurrence mapping uncovers three thematic clusters: digital payment adoption and acceptance; financial inclusion, financial literacy, and business performance; and the digital economy and competitiveness. The synthesis indicates that digital payment adoption enhances MSME competitiveness not directly but through the mediating mechanisms of transaction efficiency and financial inclusion, which ultimately drive business performance. The study contributes an empirically testable model and a future research agenda for digital MSME competitiveness